2020
DOI: 10.1002/ana.25728
|View full text |Cite
|
Sign up to set email alerts
|

Mean Oxygen Saturation during Sleep Is Related to Specific Brain Atrophy Pattern

Abstract: Objective: There is much controversy about the neurobiological mechanisms underlying the effects of sleepdisordered breathing on the brain. The aim of this study was to investigate the association between markers of sleeprelated hypoxemia and brain anatomy. Methods: We used data from a large-scale cohort from the general population (n = 775, 50.6% males, age range = 45-86 years, mean age = 60.3 AE 9.9) that underwent full polysomnography and brain magnetic resonance imaging to correlate respiratory variables w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
20
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 52 publications
6
20
1
1
Order By: Relevance
“…Previous research has shown that putamen is involved in sensorimotor activity (45), suggesting an important role in gating respiratory information (46). Consistent with our study, Marchi et al (47) reported that mean oxygen saturation during sleep is correlated with the volume of left putamen. Asthma often attacks during sleep, with a great influence on the oxygen saturation.…”
Section: Relationship Between Variability and Clinical Symptomssupporting
confidence: 92%
“…Previous research has shown that putamen is involved in sensorimotor activity (45), suggesting an important role in gating respiratory information (46). Consistent with our study, Marchi et al (47) reported that mean oxygen saturation during sleep is correlated with the volume of left putamen. Asthma often attacks during sleep, with a great influence on the oxygen saturation.…”
Section: Relationship Between Variability and Clinical Symptomssupporting
confidence: 92%
“…Of interest, the average sleep oxygen saturation correlated with lower brain volumes. In a large population-based study, average oxygen saturation during sleep correlated with lower brain volumes in the hippocampus-amygdala complex and other cortical regions sensitive to low oxygen saturation [41]. These findings suggest that nocturnal oxygen saturation could be a better metric to study brain health in OSA patients.…”
Section: Discussionmentioning
confidence: 78%
“…In a large population based study, oxygen levels during sleep correlated with brain volumes in the hippocampusamygdala complex and other cortical regions sensitive to hypoxemia. [42] These findings suggest that nocturnal oxygenation or hypoxemia may serve as better predictors of brain health. In addition, we observed that daytime sleepiness, as measured by the Epworth sleepiness scale (ESS), had positive correlations with the lateral ventricles, suggesting an increment in ventricular volume with increase daytime sleepiness.…”
Section: Discussionmentioning
confidence: 96%